Looking at upside-down ants: Taxonomic revision of the Neotropical species of Odontomachus Latreille, 1804 (Hymenoptera: Formicidae: Ponerinae) - França, Eder Cleyton Barbosa; Fernandes, Itanna Oliveira; Bravo, John Edwin Lattke (Zootaxa, 2024)
We provide a taxonomic revision of the Neotropical species of Odontomachus, including description of gynes, their wing venation, and description of males. We examined 2633 workers, 156 gynes, and 142 males, resulting in four new species, which are described here: O. chicomendesi sp. nov., O. cupreus sp. nov., O. dubius sp. nov. and O. xeta sp. nov. We propose the synonym of O. mayi n. syn. under O. panamensis, resulting in 27 species of Odontomachus in the neotropics. Dichotomous keys, illustrated with high quality images, are provided for workers, gynes, and males. We describe/redescribe 21 gynes and 15 males. The worker of O. allolabis is redescribed and the status of the type specimens as parasitized is confirmed. Odontomachus chelifer shows wide variation of the petiolar node, metasternal process and male propodeum sculpturing indicating that it is possibly a complex of cryptic species. The metasternal process is an important diagnostic character for most of the species. The morphology of the worker and gynes are congruent with the current molecular phylogeny for the genus. We discuss the hastatus and haematodus species groups relationships and keep O. cornutus, O. mormo, and O. bradleyi in their respective monospecific groups. It is still necessary to investigate male genitalia to shed light on the relations within the haematodus group and detect possible cryptic species.